Global leaf nitrogen and phosphorus stoichiometry and their scaling exponent. Issue 5 (15th December 2017) - Tian, Di; Yan, Zhengbing; Niklas, Karl J; Han, Wenxuan; Kattge, Jens; Reich, Peter B; Luo, Yongkai; Chen, Yahan; Tang, Zhiyao; Hu, Huifeng; Wright, Ian J; Schmid, Bernhard; et al.
Abstract: Leaf nitrogen (N) and phosphorus (P) concentrations constrain photosynthetic and metabolic processes, growth and the productivity of plants. Their stoichiometry and scaling relationships regulate the allocation of N and P from subcellular to organism, and even ecosystem levels, and are crucial to the modelling of plant growth and nutrient cycles in terrestrial ecosystems. Prior work has revealed a general biogeographic pattern of leaf N and P stoichiometric relationships and shown that leaf N scales roughly as two-thirds the power of P. However, determining whether and how leaf N and P stoichiometries, especially their scaling exponents, change with functional groups and environmental conditions requires further verification. In this study, we compiled a global data set and documented the global leaf N and P concentrations and the N:P ratios by functional group, climate zone and continent. The global overall mean leaf N and P concentrations were 18.9 mg g −1 and 1.2 mg g −1, respectively, with significantly higher concentrations in herbaceous than woody plants (21.72 mg g −1 vs. 18.22 mg g −1 for N; and 1.64 mg g −1 vs. 1.10 mg g −1 for P). Both leaf N and P showed higher concentrations at high latitudes than low latitudes. Among six continents, Europe had the highest N and P concentrations (20.79 and 1.54 mg g −1 ) and Oceania had the smallest values (10.01 and 0.46 mg g −1 ). These numerical values may be used as a basis for the comparison of other individual studies. Further, we found that the scaling exponent varied significantly across different functional groups, latitudinal zones, ecoregions and sites. The exponents of herbaceous and woody plants were 0.659 and 0.705, respectively, with significant latitudinal patterns decreasing from tropical to temperate to boreal zones. At sites with a sample size ≥10, the values fluctuated from 0.366 to 1.928, with an average of 0.841. Several factors including the intrinsic attributes of different life forms, P-related growth rates and relative nutrient availability of soils likely account for the inconstant exponents of leaf N vs. P scaling relationships.